Kepuasan kerja sebagai mediasi efek locus of control terhadap kedisiplinan karyawan - Eka Kurniawati; Endi Sarwoko; Endah Andayani (Jurnal Ekonomi Modernisasi, 2021)
The aim of the study was to investigate the effect of locus of control on employee discipline and the role of job satisfaction in mediating the relationship of locus of control on employee discipline. This study uses a quantitative approach, the research was conducted at YPI Miftahul Huda Papar, Kediri Regency, data was collected using a questionnaire filled out by all employees. Locus of control is measured by the ability, interest, effort, fate, and influence of others. Job satisfaction is measured by using 2 factors motivation, the last work discipline includes goals, justice, inherent supervision, sanctions and punishments. Data were analyzed for hypothesis testing using Path Analysis. The results of the analysis reveal that locus of control and job satisfaction have an effect on employee discipline. Another finding is that job satisfaction plays a role in mediating the influence of locus of control on work discipline. Suggestions for further research is to develop this research in a different place and examine the consequences of work discipline.